HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN LITERASI INFORMASI KOSMETIKA PADA MAHASISWA DI ERA MEDIA SOSIAL : TINJAUAN LITERATUR - Selvi Revila; Yosi Meidiawati (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
In the current era of technological development, the use of social media among students is increasingly popular for seeking information, including about cosmetics. This study aims to analyze the relationship between emotional intelligence and cosmetic informatics literacy among students in the social media era. This study is included in qualitative research using literature studies. This study was conducted on research journal articles with keywords emotional intelligence and literacy. The articles analyzed have criteria consisting of; (1) Articles with publication years 2020-2025, (2) Included in national and international journals, (3) Relevant to the research topic. The research was conducted by means of literature studies. The collected data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study obtained that overall the findings of previous studies stated that emotional intelligence has a positive and significant relationship with informatics literacy. Students who have high emotional intelligence tend to be wiser and more critical in sorting cosmetic information on social media. This finding confirms that strengthening emotional intelligence can be an important step in improving students' digital literacy, especially amidst the current rapid flow of cosmetic information.